2016
DOI: 10.1590/s1984-29612016070
|View full text |Cite
|
Sign up to set email alerts
|

Does hair coat length affect flea infestation in naturally infested dogs?

Abstract: The Siphonaptera are parasitic insects of endothermic animals and Ctenocephalides felis and Pulex irritans are important parasites of dogs. This study evaluated the effect of hair coat length and time of year on the population size of C. felis and P. irritans in naturally infested dogs. Fleas were collected from 14 dogs on a monthly basis for a year (February 2015 to January 2016) at a rural property in Bagé, Rio Grande do Sul, Brazil. The dogs were divided into two groups based on hair coat length: short co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The Pulicidae may be changing its habits of seeking the host only for feeding (LINARDI, 2011), as the canine host also provides protection against abiotic conditions. In another study (SILVA et al, 2016), our research group, has shown the preference of P. irritans for long-haired dogs, confirming a trend for this flea to remain in the dogs, thus changing their eating behavior. Furthermore, the increase of P. irritans population during periods when the population of C. felis decreased may indicate that P. irritans is host-opportunistic and occupies a niche left by the hostspecific C. felis, when the latter species has its population smaller due to unfavorable abiotic conditions.…”
Section: Resultssupporting
confidence: 54%
“…The Pulicidae may be changing its habits of seeking the host only for feeding (LINARDI, 2011), as the canine host also provides protection against abiotic conditions. In another study (SILVA et al, 2016), our research group, has shown the preference of P. irritans for long-haired dogs, confirming a trend for this flea to remain in the dogs, thus changing their eating behavior. Furthermore, the increase of P. irritans population during periods when the population of C. felis decreased may indicate that P. irritans is host-opportunistic and occupies a niche left by the hostspecific C. felis, when the latter species has its population smaller due to unfavorable abiotic conditions.…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, it is likely that many owners buy anti-parasitic treatments over the counter, so it is not clear how accurately veterinary clinical data represents the true prevalence of parasite infestation. It is unclear why Labrador Retrievers have protection to parasite infection, but it could be due to their characteristically short coat-type, which has been associated with reduced likelihood of tick infestation 89 and flea infestation 90 in dogs, perhaps due to easier removal of the parasite during grooming (by the dog or owner) or due to the increased difficulty for the parasite to attach and grip to the coat. Labrador Retrievers’ affinity to water might also help to remove external parasites, especially if they are often bathed or allowed to swim outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, dogs from a farm in Brazil were surveyed for 1 year and two species of flea collected, C. felis and P. irritans . The number of cat fleas was significantly greater on long haired dogs than on short haired dogs [ 95 ]. Of 292 cats submitted to a spay/neuter program, 60% were infested with C. felis [ 96 ].…”
Section: Cat Flea Biology and Ecologymentioning
confidence: 99%